INTO THE DARKNESS AND SILENCE: EVISCERATION IN A DEAF-MUTE- BLIND PATIENT WITH NEGLECTED GLAUCOMA: Poster Presentation - Case Report - Resident - Lumita, Ferdinand Inno; Laksmita, Yulinda Arty; Sieman, Andrew John; Iskandar, Ferdy; Paramita, Carennia; Aziza, Yulia (Majalah Oftalmologi Indonesia, 2023)
Introduction : Glaucoma can have a potentially devastating effect on patient’s vision and quality of life if not treated properly. We described a neglected glaucoma case in a deaf-mute-blind patient that leads to evisceration. Case Illustration : A 64-year-old deaf-mute female came to our emergency room with chief complaint of bloody discharge from her right eye 12 hours prior to admission with no history of trauma. Patient’s right eye has been blind for the last four years; her left eye has been nonfunctional since she was in her 30s. She went to a primary clinic during this time but did not get any diagnoses. Physical examination revealed uveal prolapse of the right eye with infiltrates around the remaining cornea; and phtisical left eye with IOP of 30 mmHg and opaque cornea. We performed evisceration with dermato-fat graft of the right eye. Discussion : Glaucoma is a challenging disease, especially in developing countries. It is difficult to diagnose due to its nature to be asymptomatic until late in the disease course. The loss of vision is painless and insidious; resulting in late diagnosis unless patients are screened for glaucoma early on. Patient in this report is particularly difficult for the caretaker since she is a deaf-mute patient; resulting in a suspected undiagnosed glaucoma that leads to evisceration and blindness. Conclusion : Glaucoma care generally necessitates routine follow-up for monitoring of disease progression and medication adjustments. Good screening system, family support, and integration of eye care into existing healthcare systems is needed for early detection to reduce blindness from glaucoma.